Contrastive Analysis of Bilingual and Monolingual EFL Learners' Syntactic Errors in Translation - Mohammadi, Ehsan (2020)
This study aimed at the analysis of syntactic errors in translation done by both bilingual and monolingual EFL learners. Research on the subject of the study implied that there might be differences between monolinguals and bilingual learners of foreign languages. The gaps of studies on differences between monolinguals and bilingual’s translations from Persian into English language presumed as research question of the study. Through a quantitative and experimental analysis, the researcher collected data from two universities of IAU of South Tehran (monolingual) and Jihad University of Kermanshah (bilingual) using students majoring in translation studies. The OPT test was applied to specify eligible students for the study and then a Persian literary text was offered to students to measure their syntactic errors as introduced by Keshavarz’s (1996) model of error analysis. From 100 participants 36 monolinguals and 24 bilinguals were eligible for the study whose translations were scored by the two raters. The results of the study indicated that there is a significant difference between the scores of monolingual and bilingual translators. In addition, the rate of literal errors and approximation was more than other errors that were reported as the result of language learning strategies and communicative strategies. However, new studies are suggested to investigate the types of errors made by monolinguals and bilinguals and graduate students with advanced level of language learning.